2013
DOI: 10.3390/metabo3010101
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Changes in Synechocystis PCC6803 upon Nitrogen-Starvation: Excess NADPH Sustains Polyhydroxybutyrate Accumulation

Abstract: Polyhydroxybutyrate (PHB) is a common carbon storage polymer among heterotrophic bacteria. It is also accumulated in some photoautotrophic cyanobacteria; however, the knowledge of how PHB accumulation is regulated in this group is limited. PHB synthesis in Synechocystis sp. PCC 6803 is initiated once macronutrients like phosphorus or nitrogen are limiting. We have previously reported a mutation in the gene sll0783 that impairs PHB accumulation in this cyanobacterium upon nitrogen starvation. In this study we p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
70
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 37 publications
10
70
1
Order By: Relevance
“…After the LC shift, the carboxysome number increased in both strains, the wild type and the D4 mutant. Additionally, the D4 mutant also had more PHB bodies under HC conditions, which is characteristic for Synechocystis 6803 wild-type cells exposed to carbon excess under high-light conditions, leading to a reducing intracellular environment (Hauf et al, 2013). In addition to Ci-specific genes, a transcript subset indicated a general stress response of D4.…”
Section: Resultsmentioning
confidence: 91%
“…After the LC shift, the carboxysome number increased in both strains, the wild type and the D4 mutant. Additionally, the D4 mutant also had more PHB bodies under HC conditions, which is characteristic for Synechocystis 6803 wild-type cells exposed to carbon excess under high-light conditions, leading to a reducing intracellular environment (Hauf et al, 2013). In addition to Ci-specific genes, a transcript subset indicated a general stress response of D4.…”
Section: Resultsmentioning
confidence: 91%
“…6). Hauf et al (2013) have shown that the reduction state of the cofactor pool can influence PHB production. PHB production observed here could be the result of an increased level of NAD(P)H and indirectly be a way to deal with NAD + photoreduction (Herter et al, 1998), notably occurring at the beginning of the growth curve.…”
Section: Resultsmentioning
confidence: 99%
“…In the last step of biosynthesis, hydroxybutyryl-CoA is polymerized to polyhydroxybutyrate by a class III PHB synthase, which is a heterodimer of PhaE (slr1829) and PhaC (slr1830) that builds the catalytically active enzyme in cyanobacteria (11). The PhaEC heterodimer (12) (or tetramer [13]) synthesizes PHB, thereby building up PHB granules, to which it is attached (4). This marks the boundaries of our understanding of PHB accumulation in cyanobacteria on a molecular level.…”
mentioning
confidence: 99%
“…This metabolite can be utilized for either gluconeogenesis or glycolysis, providing the necessary carbon skeletons for biosynthesis of amino acids and other metabolites required for cell growth (2), when growth conditions are suitable and nutrients are abundant. In fact, carbon flux is greatly affected by the availability of macronutrients like nitrogen (3)(4)(5) and phosphorus, which may limit growth (6). Under nutrient-limiting conditions, cyanobacteria undergo a stress adaptation process termed chlorosis (7).…”
mentioning
confidence: 99%